Cooperative Learning Strategy in teaching Arabic for Non Native Speakers - Suo Yan Mei; Suo Yan Ju; Ayishah Binti Mohd (Humanities Today: Proceedings, 2022)
Cooperative learning is a teaching strategy that can help students to be successful in academic achievement and skills, as well as can assist the students to enhance the social interaction and human relation; however, this research explored the cooperative learning strategy in teaching Arabic for non native speakers, and will show the experiences for Arabic lecturers during their applying this method for teaching Arabic at sultan Idris education university Malaysia. The researchers will depend on the survey research design. The study will use a sample of 10 lecturers who are teaching Arabic language randomly selected from Sultan Idris education University Malaysia. The method will use data collection which included a 10-items questionnaire. Results show that majority of lecturers strongly support to apply the cooperative learning during the classes and outside of classes to help the students to improve their language skills, communication skills and social interaction.